Comparison of functional results of nerve graft, vein graft, and vein filled with muscle graft in end-to-side neurorrhaphy - (:unkn) unknown (WILEY-LISS, 2003)
End-to-side neurorrhaphy is an alternative method in the situation where the proximal part of the nerve cannot be found. When the intact nerve is not close enough to perform end-to-side neurorrhaphy, it will be necessary to use a graft for transporting the regenerating axons. In this study, we tried to find out whether it is possible to use a graft in an end-to-side neurorrhaphy, and compared the nerve graft with possible alternative grafts, i.e., vein and muscle-filled vein grafts. Thirty male Sprague Dawley rats were used, with an average weight of 293 g (range, 250-350 g). All experiments were done on the right side. A 2-cm nerve graft, beginning 1 cm distal to the branching level, was sectioned from the peroneal nerve. A 1-mm epineural window was opened in the tibial nerve. In the first group, the proximal side of this graft was sutured to the tibial nerve side in an end-to-side fashion, and the distal side was sutured to the distal peroneal nerve stump in an end-to-end fashion. In the second group, the right 2-cm jugular vein was harvested, and was used to bridge the defect instead of the nerve graft used in the first group. In the third group, a 2-cm jugular vein filled with fresh skeletal muscle was used to bridge the defect. At 2, 4, 8, 12, 20, and 28 weeks, functional assessment of nerve regeneration was performed, using walking-track analysis. The numbers of myelinated fibers and fiber diameters were measured, and an electron microscopic evaluation was carried out. Based on walking-track analysis and fiber diameters, the differences of all three groups were statistically significant (P < 0.05). While the differences of myelinated fibers between the first and second groups were not significant, the differences between the rest (group 1-group 3 and group 2-group 3) were significant (P < 0.05). Our study showed that, in end-to-side neurorrhaphy, the use of a nerve graft is possible, and a vein graft is also a good alternative, but a muscle-filled vein graft is not.
Keywords: SILICONE CHAMBERS; AUTOGENOUS VEIN; TRACK ANALYSIS; GROWTH-FACTOR; REGENERATION; REPAIR; RAT; SPECIFICITY; CONDUIT